Synthesis and structures of organotin(IV) complexes and their catalytic addition of arylamines into N, N′-diisopropylcarbodiimide. (1st July 2019) - Guo, Zeling; Tian, Dan; Yang, Qiaokun; Tong, Hongbo; Wang, Yingying; Zhou, Meisu
Graphical abstract: Two organotin(IV) complexes were synthesized and characterized. Their catalytic properties in the addition of arylamines to N, N′ -diisopropylcarbodiimide have been evaluated. Abstract: Organotin(IV) complexes [N(Ph)C(NMe2 )NC(NMe2 )N(SiMe3 )]2 SnCl2 (1 ) and [N(SiMe3 )C(NMe2 )NC(NMe2 )N2 Sn]2 (2 ) bearing 1, 3, 5-triazapentadienyl ligands were synthesized and fully characterized. Their structures confirmed by single-crystal X-ray diffraction studies. The catalytic properties of1 and2 as pre-catalysts in the addition of aniline or 2, 6-diisopropylaniline to N, N′ -diisopropylcarbodiimide have been evaluated.